MOTIVATION IN LANGUAGE LEARNING - Musurmonkulova Indira (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This article delves into the various factors influencing motivation in language learning, highlighting the significance of intrinsic and extrinsic motivators. It examines theories such as Gardner's Socio-Educational Model and Deci and Ryan's Self-Determination Theory, which underscore the role of personal interest, cultural integration, and emotional engagement in language acquisition. The research presents empirical evidence from surveys and case studies demonstrating that motivated learners are more likely to achieve fluency and maintain language skills over time. Additionally, the article discusses practical implications for educators, suggesting strategies to foster motivation through goal setting, interactive activities, and cultural exposure. Overall, it emphasizes that understanding motivation is critical for developing effective language teaching methodologies and enhancing student engagement.